Enhancing Safety in Regional Anesthesia: Guidelines from the Italian Society of Anesthesia, Analgesia, Resuscitation and Intensive Care (SIAARTI) - Vito Torrano; Salvatore Anastasi; Eleonora Balzani; Enrico Barbara; Astrid Ursula Behr; Mario Bosco; Claudio Buttarelli; Silvia Bruletti; Dario Bugada; Chiara Cadeddu; Gianluca Cappelleri; Luigi Cardia; et al. (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Background Regional anesthesia techniques have become integral to modern perioperative care, offering enhanced pain management and recovery outcomes. However, their application in patients with specific conditions, such as anticoagulation therapy or preexisting comorbidities, raises concerns regarding safety and efficacy. Current guidelines addressing these issues are fragmented, necessitating comprehensive, evidence-based recommendations. Methods A multidisciplinary panel of experts in anesthesiology and pain management was convened under the auspices of the Italian Society of Anesthesia, Analgesia, Resuscitation, and Intensive Care (SIAARTI). The guidelines presented herein were developed according to the GRADE system (Grading of Recommendations of Assessment Development and Evaluations), in compliance with the methodological manual for the production of clinical practice guidelines published by the National Center for Clinical Excellence, Quality, and Safety of Care, Italian National Institute of Health. Results The guidelines encompass recommendations on neuraxial blocks in anticoagulated patients, the dual guidance use in peripheral nerve blocks, the role of sterile field preparation, and post-procedural monitoring. Evidence from meta-analyses and large-scale observational studies supported most recommendations, though limitations in study heterogeneity were noted. Conclusions These guidelines provide a structured framework for clinicians to enhance patient safety and procedural efficacy in regional anesthesia. Further research is encouraged to address identified gaps, particularly regarding specific patient subgroups and novel regional anesthesia techniques.